The Impact of COVID-19 on Instruction for and the Implementation of Quebec’s Sexual Health Curriculum: Teacher Perspectives - Kathol, Katja; Leung, Enoch; Flanagan, Tara (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2023)
In March 2020, the COVID-19 pandemic necessitated school closures across Quebec. Educators shifted to online learning and complied with COVID-19 safety measures for in-person teaching, impacting the implementation of Quebec’s Sexuality Education program. Drawing on responses from a sample of 165 in-service teachers working in English school boards across Quebec, this study discusses the challenges that characterized teaching sexual health education (SHE) during the COVID-19 pandemic. The data analyzed in this study consist of teachers’ responses to one qualitative question: How has the COVID-19 situation affected your teaching and incorporation of Quebec’s comprehensive sexual health education curriculum in your classroom? The results indicate that educators taught less SHE during the COVID-19 pandemic due to a lack of time and other core curriculum subjects taking precedence. Other challenges were present, including a lack of clarity from school administrators on how SHE should be implemented, reduced ability to supplement SHE classes with guest speakers, difficulty facilitating discussions due to students’ home environments, and decreased student engagement. Despite these barriers, teachers felt that teaching SHE during the COVID-19 pandemic was important and expressed the need for more pedagogical development and training opportunities to improve SHE both online and in person.